SomPack: succession planning gone wrong. Issue 2 (21st May 2021) - Dube, Manu; Dube, Sema
Abstract : Learning outcomes: The case, while acknowledging the difficulty of managing a family business in view of the accompanying human issues, emphasizes that sound business practices and procedures, and clarity with regard to the goal, remain the key; a firm is a complex, interconnected system and management needs a systems viewpoint; and technology can only support underlying business processes if there is clarity with respect to these. Case overview/synopsis: SomPack had survived low-cost Asian competition starting the mid-1990s, a revolt by some extended family to try and bring it down with the help of a competitor, the Turkish banking crisis of 2001, and the global economic crisis of 2008 all the while watching its suppliers, competitors and customers collapse. A focus on cost-cutting and internal discipline by the successor, who had been promoted to CEO in 2004, had exacerbated internal discontent somewhat and had led to issues with production planning, but everyone understood that times were tough. Several large customers who had left were asked to return because the alternatives had been worse. By 2012, SomPack was considering expansion into new products in collaboration with its international partners. Then one day, in July 2013, it suddenly collapsed. Could the entire approach have been wrong? What should management have done instead? Complexity academic level: Undergraduate, graduate business management. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 7: Management Science.